A Descriptive Study of Segmental Phonological Features in American and Singapore English - Shidqiyah, Meyla; Prasetyo, Yudy; Aisyah, Siti (JELITA, 2026)
This study aims to describe the segmental phonological features found in the speech of Abele’s American English and Roger’s Singapore English as represented in the Clash of Champions program by Ruangguru. The study employs a descriptive qualitative approach and analyzes naturally occurring speech produced by two speakers featured in the program. The findings indicate that Roger’s speech, representing Singapore English, consistently demonstrates non-rhoticity, vowel centralization, shortened vowel duration, and diphthong reduction. In contrast, Abele’s speech, representing American English, consistently exhibits rhoticity, full diphthongization, and clear tense–lax vowel distinctions, aligning with General American English patterns. These segmental features appear systematically in spontaneous discourse, suggesting that accent-specific segmental phonological patterns are deeply internalized. This study contributes to the understanding of phonological variation within World Englishes by examining authentic spoken interaction rather than isolated speech samples.